GASOLINE SPECIFICATIONS IN THE ASEAN COUNTRIES - E. Jasjfi (Testing Center for Oil and Gas LEMIGAS, 1986)
Gasoline is one of the most important petroleum products which is directly used by a large section of the general public. Countries of the Southeast Asia have been cooperating closely in many fields, including the petroleum industry. In view of the facts, it would be of prime interest to examine and compare the gasoline specifications in the ASEAN countries. This paper presents the results of the study, based on the official standard specifications in force in five ASEAN countries. The similarities and differences are emphasized, as well as their significance.